The father-daughter plot : Japanese literary women and the law of the father - Copeland, Rebecca L., 1956-; Ramirez-Christensen, Esperanza U. (Honolulu, Hawaii : University of Hawai'i Press, 2001)
This provocative collection of essays is a comprehensive study of the "father-daughter dynamic" in Japanese female literary experience, Its contributors, representing a new generation of scholars of Japanese literature, examine the ways in which women have been placed politically, ideologically, and symbolically as "daughters" in a culture that venerates "the father." They weigh the impact that this daughterly position has had on both the performance and production of women's writing from the classical period to the present
Of love and bondage in the Kagerō diary : Michitsuna's mother and her father / Sonja Arntzen -- Self-representation and the patriarchy in the Heian female memoirs / Esperanza Ramirez-Christensen -- Towazugatari : unruly tales from a dutiful daughter / Edith Sarra -- Mother tongue and father script : the relationship of Sei Shōnagon and Murasaki Shikibu to their fathers and Chinese letters / Joshua S. Mostow -- De-siring the center : Hayashi Fumiko's hungry heroines and the male literary canon / Janice Brown -- A room sweet as honey : father-daughter love in Mori Mari / Tomoko Aoyama -- Enchi Fumiko : female sexuality and the absent father / Eileen B. Mikals-Adachi -- Needles, knives, and pens : Uno Chiyo and the remembered father / Rebecca L. Copeland -- A Confucian utopia : Kōda Aya and Kōda Rohan / Ann Sherif -- Ōba Minako and the paternity of maternalism / Sharalyn Orbaugh -- Kurahashi Yumiko's negotiations with the fathers / Atsuko Sakaki -- Ogino Anna's gargantuan play in Tales of peaches / Midori McKeon.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Japanese literature -- Women authors -- History and criticism; Fathers and daughters in literature; Pères et filles dans la littérature.; LITERARY CRITICISM -- Asian -- General; LITERARY CRITICISM -- Asian -- Japanese; Fathers and daughters in literature; Japanese literature -- Women authors; Schriftstellerin; Tochter; Vater; Geschichte; Aufsatzsammlung; Japan; Japans; Letterkunde; Vrouwelijke auteurs; Vaders; Dochters; Littérature japonaise -- Femmes écrivains -- Histoire et critique; Frères et soeurs -- Dans la littérature.; 18.87 Japanese language and literature; Criticism, interpretation, etc